Jihad Perspektif Hizbut Tahrir Indonesia - Azman, Azman (Al-Daulah : Journal of Criminal Law and State Administration Law, 2015)
Hizbut Tahrir Indonesia is Islamic mass organization. Politics is the activity, and Islam is its ideology. Hizbut Tahrir engaged in the midst of people, struggling to make Islam the primary court, and lead them to re-establish the Caliphate and enforce the law according to what Allah has revealed in life. Hizbut Tahrir interpret jihad as an effort to mobilize all abilities in war for the sake of Allah to raise the requires, spreading the message of Islam, as well as assist with the the treasure, the opinions, directly multiply the line, and others. “Cramped” meanings of this the word of jihad, finally limiting its actualization only on physical jihad, both defensive as well as offensive. To Hizbut Tahrir Indonesia, a main objective of the establishment of the caliphate is total implementation of Islamic law, which both are preconditions to do offensive jihad.